2020
DOI: 10.1088/1748-9326/ab6c30
|View full text |Cite
|
Sign up to set email alerts
|

Greenspace, bluespace, and their interactive influence on urban thermal environments

Abstract: Urban land use land cover (LULC) change raises ambient temperature and modifies atmospheric moisture, which increases heat-related health risks in cities. Greenspace and bluespace commonly coexist in urban landscapes and are nature-based heat mitigation strategies. Yet, their interactive effects on urban thermal environments are rarely assessed and it remains unclear how extreme heat events (EHEs) affect their ability to regulate human thermal comfort. Using multi-year observations from a dense urban observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…We found that the daytime spatial variation of the canopy temperature is much higher than nighttime variation. The finding underlines the great sensitivity of the daytime canopy temperature to the surrounding environment, which coincides with diurnal patterns of LST 31 , 40 . This research has found a greater impact of urban greenspaces compared to urban bluespaces and building height on modulating daytime canopy temperature.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…We found that the daytime spatial variation of the canopy temperature is much higher than nighttime variation. The finding underlines the great sensitivity of the daytime canopy temperature to the surrounding environment, which coincides with diurnal patterns of LST 31 , 40 . This research has found a greater impact of urban greenspaces compared to urban bluespaces and building height on modulating daytime canopy temperature.…”
Section: Discussionsupporting
confidence: 68%
“…Previous findings revealed the enhanced cooling effects of greater greenspace coverage on urban ambient temperature 31 , 33 , 34 . A similar relationship is observed between GAF and the canopy temperature diurnally, showing a greater greenspace coverage associated with a cooler canopy temperature (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations